Genetic Association Analysis of Paratuberculosis Forms in Holstein-Friesian Cattle. (19th May 2014) - Vázquez, Patricia; Ruiz-Larrañaga, Otsanda; Garrido, Joseba M.; Iriondo, Mikel; Manzano, Carmen; Agirre, Mikel; Estonba, Andone; Juste, Ramón A.
Abstract : A genetic susceptibility to Mycobacterium avium subsp. paratuberculosis (MAP) infections in ruminants has been longtime suspected to exist. Recently, natural infections in cattle have been reclassified into latent and patent forms based on histopathological findings and their associations with immunological and microbiological variables. This study aims to explore whether these newly defined phenotypes are associated with twenty-four single-nucleotide polymorphisms (SNPs) in six bovine candidate genes: nucleotide-binding oligomerization domain 2 (NOD2), solute carrier family 11 member A1 (SLC11A1), nuclear body protein SP110 (SP110), toll-like receptors (TLRs) 2 and 4, and CD209 (also known as DC-SIGN, dendritic cell-specific ICAM3-grabbing nonintegrin ). SNPs were genotyped for 772 Holstein-Friesian animals (52.6% apparently free ; 38.1% latent ; 9.3% patent ) by TaqMan OpenArray technology. Genotypic-phenotypic associations were assessed by logistic regression analysis adjusted for age at slaughter, under five models (codominant, dominant, recessive, overdominant, and log-additive), and corrected for multiple testing. The rs208222804 C allele ( CD209 gene) was found to be associated with latent paratuberculosis (log-additive model: P < 0.0034 after permutation procedure; OR = 0.64, 95% CI = 0.48–0.86). No significant association was detected between any SNP and the patent phenotype. Consequently, CD209 gene may play a key role in the pathogenesis of bovine paratuberculosis.